Adaptation determinants of artificial intelligence in small and medium enterprises - Sylwia Bąk; Piotr Jedynak; Przemysław Kaczmaryk (European Management Studies)
Purpose: Small and medium enterprises (SMEs) are increasingly using artificial intelligence (AI) in their operational and strategic activities. In order to properly prepare for the processes of AI implementation and to plan the path of digital transformation using the tools it supports, enterprises need to be fully aware of the factors that determine a successful implementation of the processes. The aim of this text is to identify the key determinants related to the adaptation of AI tools and technologies in business processes and operations of SMEs. Design/methodology/approach: In order to establish a catalog of adaptation determinants of artificial intelligence in SMEs, 24 deliberately selected academic texts indexed in the EBSCO database and published between 2021 and 2023 were analyzed. The research methods that were used are: an exploratory research approach and a single-step logical classification method, fulfilling the required criteria of exhaustiveness and separability in the selection. Findings: Using an exploratory approach to literature research, we identified 55 different factors impacting AI adaptation in SMEs, which we divided into the following seven categories, using a logical classification method: strategy and business model, culture and attitude, resources, support, entrepreneurship and innovation, competitive position and environmental conditions. Research limitations/implications: The research results have theoretical and practical implications. In the theoretical aspect, they can be a starting point for searching for methods to deal with identified determinants. In a practical aspect, the identified conditions may constitute a guide for SMEs planning to implement AI tools. A research limitation may be the fact that due to the dynamic development of the technological environment of SMEs, the identified catalog of determinants is certainly not closed. Originality/value: The added value of the conducted research mainly concerns the identification and categorization of adaptation determinants of implementing AI in SMEs, which can significantly contribute to increasing the awareness of the SMEs about the challenges they face on the path of digital transformation.